Molecular Characteristics of Cytochrome B for Mackerel Barcoding - Deden Yusman Maulid; Mala Nurilmala; Nurjanah Nurjanah; Hawis Maddupa (Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2016)
Cytochrome b (cyt b) is one of the genes in mitochondrial DNA that is often used as a molecularmarker to identify species through DNA Barcoding. The aim of the present study was to investigate thebioinformatic of cyt b that isolated from mackerel fish. PCR amplification showed the length of DNA cytb from king mackerel was 803 bp within purine 312 bp and pyrimidine 491 bp while Korean mackerel 791bp within purine 316 bp and pyrimidine 475 bp. Phylogenetic analysis showed all sample join in mackerelgroups (Scomberomorus commerson and Scomberomorus koreanus). The Isoelectric point value of cyt b fromking mackerel is 6.38 and molecular weight is 29826.23; Korean mackerel are 8.67 and molecular weight is29372.77. Hydrophaty plot showed cyt b of mackerel more hydrophobic. Based on 3D modelling both ofthem have eight different sections showing by different colors.Keywords: characteristic molecular, cytochrome b, Mackerel